Getting to Know Fermented Foods: Benefits and Effects on Digestive Health - Lovi Sandra (Pt. Anagata Sembagi Education, 2024)
Fermented foods, which have become an integral part of culinary traditions around the world, are gaining increasing attention as foods that support digestive health. In Indonesia, tempeh and tape are widely recognized examples of fermented foods, while in other countries there is kimchi and sauerkraut. This phenomenon is driven by a growing awareness of the importance of a healthy gut microbiota, which contributes to nutrient absorption, immune system strengthening and reduced risk of digestive disorders. This study used a descriptive qualitative approach to explore the benefits and influence of fermented foods on digestive health, involving 20 subjects from various backgrounds, including producers, consumers, nutritionists and cultural observers. The results showed that fermented foods such as yogurt, kefir and kombucha are rich in probiotics that benefit the balance of gut microbiota. In addition, fermented foods also play an important role in cultural preservation and adaptation to the modern food industry. In the context of globalization, fermented foods are not only part of a healthy diet, but also a worldwide symbol of cultural identity. This research is expected to provide deeper insights into the contribution of fermented foods to digestive health and a healthy lifestyle